Principles of Online Learning Assessment: A Literature Review Between Western Education Theory and Islamic Education Theory - Ardiansyah, Arief; Al Anshori, Thoriq; Zakaria, Zukhkriyan; Cahyanto, Bagus (Jurnal Pendidikan Agama Islam, 2022)
Purpose – The right assessment strategy can reduce the number of academic dishonesties during online learning in the pandemic era. Academic dishonesty is a problem considered normal but has a detrimental impact on the development of a nation. Therefore, instructors need to know the principles of assessment that can reduce the number of academic dishonesties in universities. Design/methods/approach – This study uses a qualitative approach with a literature study technique. This literature comes from several online assessment books, articles, handbooks, and others. The procedure used in this study involves selecting a topic, developing themes, selecting problems, searching for literature in the database, and selecting and evaluating literature based on these problems. Findings – The results of this study are in the form of online learning assessment principles that can be applied in designing assessment activities. First, design a student-centered assessment that includes self-reflection. Second, design and include grading rubrics for assessing contributions to the discussion and assignments, projects, and the collaboration itself. Third, include collaborative assessment. Fourth, encourage students to develop skills in providing feedback. Fifth, use assessment techniques appropriate to the context and learning objectives. Sixth, design an assessment that is clear, easy to understand, and guaranteed success in the online environment. Seventh, ask students for input on how the assessment is carried out. Research implications – This study contributes to the development of literature regarding the online learning assessment process, especially in universities. Originality/value – Future research should be able to test these online learning assessment principles to find empirical evidence of their effectiveness.